Characterization of hydrogeological units and hydrodynamics of a section of the aquifer system in the city of Cartago, Costa Rica - Ramírez-Granados Pablo Ignacio (Geološki Anali Balkanskoga Poluostrva)
The study focuses on the hydrogeological characterization of the aquifer system in the central sector of Cartago, Costa Rica. This area was selected due to its significant urbanization and agricultural activities, both of which heavily depend on groundwater resources. The conceptual hydrogeological model was developed using well records, field hydrogeological observations along rivers and material extraction pits, macroscopic sample collection for thin-section analysis, spring and well inventories, and piezometric level analysis. A series of hydrogeological profiles were modeled to visualize the subsurface configuration of hydrogeological units and their relationships with existing geological materials. In areas with sufficient well density and ad¬equate geographic distribution, the groundwater flow dynamics within the hydrogeological units were also analyzed. The results revealed that the aquifer system consists of a variety of materials, predominantly alluvial and laharic deposits, which function as aquifer hydrogeological units. These materials contain interspersed clay lenses, fine sands, and coarse sands, which collectively influence the formation of saturated zones, aquitards, and aquicludes. Additionally, these characteristics determine the degree of confinement of the aquifer units. In some sectors, this confinement results in water upwelling, creating artesian conditions. Flow directions were predominantly oriented from north to south, following the surface gradient, although variations in flow direction highlighted the complexity and interconnectivity of the units. For the first time, the hydrogeological model of the Cartago aquifer system was defined. It comprises the Taras, La Chinchilla, Cartago, El Bosque, Tejar, and Dulce Nombre hydrogeological units. Each of these units corresponds to a specific portion of the study area within the central sector of Cartago, which lies atop the Cartago aquifer system.